The role of ADAMTS‐13 activity and complement mutational analysis in differentiating acute thrombotic microangiopathies. (11th January 2016) - Phillips, E. H.; Westwood, J. P.; Brocklebank, V.; Wong, E. K. S.; Tellez, J. O.; Marchbank, K. J.; McGuckin, S.; Gale, D. P.; Connolly, J.; Goodship, T. H. J.; Kavanagh, D.; Scully, M. A.
Abstract : Essentials Molecular diagnostics has improved the differentiation of acute thrombotic microangiopathys (TMAs). Atypical hemolytic uremic syndrome may have features mimicking thrombotic thrombocytopenic purpura. We identified novel complement mutations and a high incidence of CD46, with favorable long term outcomes. Complement mutation analysis in TMA where the diagnosis is unclear and ADAMTS‐13 activity is >10%. Summary: Background: Differentiation of acute thrombotic microangiopathy (TMA) at presentation has historically been dependent on clinical parameters. Confirmation of thrombotic thrombocytopenic purpura (TTP) is increasingly reliant on demonstrating deficient ADAMTS‐13 activity. The identification of alternative complement pathway abnormalities in atypical hemolytic uremic syndrome (aHUS), along with the proven efficacy of terminal complement inhibitors in treatment, has increased the need for rapid differentiation of TTP from aHUS. Objectives: We describe the clinical phenotype and nature of complement mutations in a cohort of aHUS patients referred as acute TMAs. Patients/methods: Fourteen consecutive aHUS patients were screened for mutations in C3, CD46, CFH, CFI, and CFB, as well as factor H (FH) antibodies. All aHUS patients had ADAMTS‐13 activity > 10%. Results: Of 14 aHUS patients, 11 (79%) had platelet counts < 30 × 10 9 /L during the acute phase. Median presenting creatinine level was 295 μmol L −1, while five (36%) of 14 presented with a serum creatinine level < 200 μmol L −1 . Alternative complement pathway mutations were detected in 9 (64%) of 14 patients, including CD46 mutations in five (36%) of 14 patients. Patients were identified with novel mutations in CFB and C3 that have not been previously reported. Conclusions: We demonstrate that diagnostic differentiation based on platelet count and renal function is insufficient to predict an underlying complement mutation in some aHUS cases. Specifically, we demonstrate a high frequency of functionally significant CD46 mutations which may mimic TTP. ADAMTS‐13 activity > 10% in a patient with a TMA should necessitate genetic screening for complement abnormalities.